2018
DOI: 10.1016/j.celrep.2018.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Membrane Structure and cAMP Compartmentation Produce Anatomical Variation in β2AR-cAMP Responsiveness in Murine Hearts

Abstract: SummaryCardiomyocytes from the apex but not the base of the heart increase their contractility in response to β2-adrenoceptor (β2AR) stimulation, which may underlie the development of Takotsubo cardiomyopathy. However, both cell types produce comparable cytosolic amounts of the second messenger cAMP. We investigated this discrepancy using nanoscale imaging techniques and found that, structurally, basal cardiomyocytes have more organized membranes (higher T-tubular and caveolar densities). Local membrane microd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 41 publications
3
54
2
Order By: Relevance
“…Cav1 and −3 contain a scaffolding domain (CSD) located in the N-terminal region suggested to interact with transmembrane adenylate cyclases (tmACs), to inhibit their activities and thus control intracellular cAMP levels (Toya et al, 1998). In cardiomyocytes, caveolae participate in the compartmentalization of intracellular cAMP which can regulate cell contractility in distal regions of the heart and, therefore, its function (Wright et al, 2014, 2018). The mechanoprotective role of caveolae is associated with the maintenance of plasma membrane integrity when both, cells and tissues, experience chronical mechanical stress (Cheng et al, 2015; Lo et al, 2015; Parton et al, 2017; Sinha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cav1 and −3 contain a scaffolding domain (CSD) located in the N-terminal region suggested to interact with transmembrane adenylate cyclases (tmACs), to inhibit their activities and thus control intracellular cAMP levels (Toya et al, 1998). In cardiomyocytes, caveolae participate in the compartmentalization of intracellular cAMP which can regulate cell contractility in distal regions of the heart and, therefore, its function (Wright et al, 2014, 2018). The mechanoprotective role of caveolae is associated with the maintenance of plasma membrane integrity when both, cells and tissues, experience chronical mechanical stress (Cheng et al, 2015; Lo et al, 2015; Parton et al, 2017; Sinha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PMU reduced the amplitude of β 2 AR-cAMP responses in the cytosol but not in the RII-PKA domains. This is an intriguing finding, as previous papers ( MacDougall et al, 2012 ; Wright et al, 2018 ) which have employed these two sensors have demonstrated that β 2 AR is a compartmentalized receptor in healthy cardiomyocytes, which will produce cAMP responses in the cell cytosol but not in the RII_PKA domains. The data we present suggest that the production of β 2 AR-cAMP is load-sensitive and may involve the loss of receptor subunits.…”
Section: Discussionmentioning
confidence: 76%
“…Cell imaging was performed with 60x oil immersion Zeiss lens, using inverted confocal laser scanning microscope (A Zeiss LSM-780), with argon laser beam at specific wavelengths for the secondary antibodies (Alexa Fluor Cav3 546 nm). Protein density and respective regularity of distribution were obtained with the same method used for TTs analysis described in more detail elsewhere ( Wright et al, 2018 ). PLA analysis was performed by automatically thresholding cell images in ImageJ (Image J Corp, United States) and utilizing default plugins to measure area covered by particles, size of particles, number of particles and number of particles per μm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current dogma is that a larger cell demands a more extensive tubular system to function which sits uneasily with data concerning species differences, the loss of T-tubules in compensatory hypertrophy in disease and the lack of correlation between atrial cardiomyocyte size and TAT density (when excluding very small cells) [40]. We demonstrated intra-chamber variability in LV cardiomyocyte TAT organisation in adult rat cells [41]. Cells derived from the apical LV increased their contractility following β2-AR activation.…”
Section: Active Mechanismsmentioning
confidence: 78%